The relationship of body mass index and T score in healthy and knee osteoarthritis women - Achmad, Anisyah; Suharjono; Soeroso, Joewono; Suprapti, Budi; Siswandono; Pristianty, Liza; Rahmadi, Mahardian; Nugraha, Jusak; Surya, Yoki; Isma, Satria Pandu Persada; Rahadiansyah, Erreza; Fahmi, Ilmia; et al. (Pharmacy Education, 2023)
Background: Osteoarthritis (OA) is a chronic, degenerative, slowly progressive disease common in women with multiple aetiology. Osteoarthritis occurs simultaneously with the reduction in bone mineral density (BMD)while a high bone mass index (BMI) value is one of the risk factors for OA. Objective: The purpose of this study was to determine the effect of BMI and BMD in healthy and knee OA women. Method: The study was conducted in an orthopaedic outpatient clinic in 2021. This is a quantitative descriptive study with accidental cross-sectional samplings. The Mann-Whitney test was used to analyse the data. Result: Subjects included in the inclusion criteria obtained 74 OA and 49 control groups. The largest subjects in the OA group were aged 56-65 years old (32, 43.24%), obese (51, 68.92%), and post-menopause (49, 66.22%). At the same time, the T score category was normal (14, 18.91%), osteopenia (22, 29.73%), and osteoporosis (38, 51.35%). Statistical analysis found a significant relationship between BMI and BMD (p = 0.002, p = 0.001) in controls and OA groups. Conclusion: Disorders of BMI and BMD are indicators of risk for OA. High BMI and low BMD values occur in women with knee OA. There is a relationship between BMI and BMD in healthy and knee OA women.